Economic and societal impacts of tornadoes - Simmons , Kevin M.; Sutter, Daniel; SpringerLink (Online service). (Boston American Meteorological Society, 2011)
Evaluates the National Weather Service's warnings and other efforts to reduce tornado casualties based on statistical analysis of data from sources such as NOAA and the U.S. Census - Provided by publisher.
What we can learn from societal impacts analysis -- Tornado climatology and soceity's tornado risk -- An analysis of tornado casualties -- Tornado warnings: how Doppler radar, false alarms, and tornado watches affect casualties -- Sheltering from the storm: evaluating tornado shelters as a mitigation investment -- Property damage and community impacts of tornadoes -- Going forward: using societal impacts research to reduce tornado risk.
Electronic reproduction.
Keywords: Tornadoes -- Economic aspects -- United States; Tornadoes -- Social aspects -- United States; Mass casualties -- Prevention. -- United States; Emergency management -- United States; Electronic books